Policy Of The Director Of Akbid Menara Bunda Kolaka Regency In Fostering Islamic Morals For Female Students - Muh. Arifin (LP2M UIN KH.Achmad Siddiq Jember, 2023)
Islam is a religion that highly upholds noble character, and this is affirmed in the hadith of the Prophet Peace Be Upon Him (SAW), stating that the primary purpose of his being sent to the human race is to perfect commendable character. As critical intellectuals who are characteristic of academics, students need to commit to the teachings of religion (Islam) and morality, which, of course, are supported by policies implemented by the campus. This study discusses the procedures the Director of the Kolaka Nursing Academy carried out in Islamic Student Moral Development. This study aims to analyze the policies applied by the Kolaka Nursing Academy Director in the Islamic Student Moral Development, supporting and inhibiting factors in Islamic Moral Development students Kolaka Nursing Academy, Effective solutions to increase students' importance on the value of diversity on campus, and life daily. This type of research is qualitative with descriptive analysis. From this study, it was produced that the policy in developing the Islamic character of Kolaka Nursing Academy students was carried out through 3 (three) stages, namely, agenda setting. Second, the quality target program will be implemented as a manifestation of the policy implementation of the Kolaka Nursing Academy Director to foster students' Islamic behavior; third, supporting factors for the development of Islamic students will be evaluated, including environmental (campus and community) factors.